Macroinvertebrate Community Structure of the River Vainganga in Gondia District, Maharashtra, India - Pralhad R. Harinkhede; Ashok P. Manekar (Journal of Indian Fisheries Association, 2016)
Macroinvertebrates offer a good source of food for fishes. Their qualitative and quantitative analysis was conducted in the river Vainganga in Gondia district from February-2010 to January 2012. A total of 62024 individuals belonging to 133 species comprising 71 families of 15 macroinvertebrate orders of Arthropoda, Mollusca and Annelida were recorded. The percent composition of macroinvertebrate taxa was found highest during winter (48.5%) followed by summer (29.6%) and lowest during monsoon (21.9%). Arthropoda emerged as a dominating phylum (87.26%) over Mollusca (10.48%) and Annelida (2.26%). The macroinvertebrate fauna was found to be dominated by Ephemeroptera (19.42%) followed by Hemiptera (16.75%), Plecoptera (16.04%) and Trichoptera (10.88%). Four diversity and two biotic indices along with %EPT (Ephemeroptera, Plecoptera and Trichoptera) and %FFGs (Functional Feeding Groups) were calculated to assess the diversity. The values of these indices indicated stable and balanced ecosystem. Upstream sites harbored higher %EPT than the downstream sites. The overall quality of water was found to be very good and habitable for aquatic organisms like fishes.